Dialogue: Bridging Personal, Community, and Social Transformation. (January 2013) - Cooper, Mick; Chak, Amy; Cornish, Flora; Gillespie, Alex
The concept and practice of dialogue has underpinned key developments in humanistic psychotherapy and counseling. However, dialogue has also been adopted by, and incorporated into, a range of educational, community and social theories and practices, and in this sense forms a valuable bridge between humanistic psychology and the wider field of sociopolitical theory and activity. This article critically reviews how the concept of dialogue has been developed and applied in four key domains, each oriented around the work of a principal theorist: psychotherapy (Martin Buber), education (Mikhail Bakhtin), community development (Paulo Freire), and social transformation (Jürgen Habermas). Drawing this analysis together, the discussion identifies three principal ways in which the term dialogue has been used: transformative, ontological, and everyday ; outlines the different levels at which dialogue can take place; and identifies key questions for further exploration.